zad 1 zapisz wyrazenia nie uzywajac nawiasów zredukuj wyrazy podobne
6x+(3x-5=
4a-(6-7a)=
(5m+8)-m=
(2p-4)-)5+9p=
-(5a-3b)+(8b-a)
potrzebuje na szybko pliss



Odpowiedź :

Amona

6x+(3x-5)= 6x + 3x - 5 = 9x - 5

4a-(6-7a)= 4a - 6 + 7a = 11a - 6

(5m+8)-m= 5m + 8 - m = 4m + 8

(2p-4)-5+9p= 2p - 4 - 5 + 9p = 11p - 9

-(5a-3b)+(8b-a) = -5a +3b +8b - a = -6a + 11b

Odpowiedź:

6x+(3x-5)= 6x + 3x - 5 = 9x - 5

4a-(6-7a)= 4a - 6 + 7a = 11a - 6

(5m+8)-m= 5m + 8 - m = 4m + 8

(2p-4)-5+9p= 2p - 4 - 5 + 9p = 11p - 9

-(5a-3b)+(8b-a) = -5a +3b +8b - a = -6a + 11b

Szczegółowe wyjaśnienie: